Zamanaşımı savunması - Ak, Aslınur (My University, 2020)
Zamanaşımı müessesesi Türk Borçlar Kanunu’nun Üçüncü Bölümü’nün İkinci Ayırımında 146 ile 161. maddeleri arasında düzenlenmiştir. Zamanaşımı medeni usul ve icra iflâs hukukunda bir savunma vasıtası teşkil eder. Çalışmamızda önce zamanaşımının hukuki niteliği, amacı ve benzer kavramlardan farkı izah edilmiştir. Zamanaşımı müessesesi hakkında yapılan tespitler doğrultusunda bir savunma vasıtası olarak ileri sürülen zamanaşımı savunmasının incelenmesi ve karara bağlanması hususları çalışmamızda ele alınmıştır. Zamanaşımının dolduğunu ileri süren borçlu karşısında alacaklının da zamanaşımının durduğunu veya kesildiğini iddia etmesi mümkün olup durma ve kesilme sebepleri medeni usul ve icra iflâs hukuku bağlamında sınırlandırılarak açıklanmıştır.

The rules relating to the extinctive prescription (statute of limitations) are to be found in the Turkish Code of Obligations, a part of the Turkish Civil Code, Arts 146 – 161. The extinctive prescription grants the obligor an exception. Turkish court precedents and scholarly opinions are in agreement that the extinctive prescription gives rise to a defence of substantive law, rather than a procedural defence, which causes the court to refrain from hearing the merits of the case. However, the extinctive prescription is such a powerful defence that, if the court upholds the defence there remains nothing else to discuss on the merits. That is to say, as the obligor does not have to perform in any case, the court shall dismiss the case due to the extinctive prescription without entering into the merits. This characteristic of the extinctive prescription gives rise to a number of procedural issues such with respect to the time limits, being considered ex officio by the court, etc. This book, an essay of master of laws is dealing with those issues.
Keywords: Civil law; Medeni hukuk; Prescription (Law); Zaman aşımı (Hukuk); Zamanaşımı Savunması Def’i İtiraz Maddi Hukuka İlişkin Savunma Vasıtaları Usul Hukukuna İlişkin Savunma Vasıtaları Zamanaşımının Kesilmesi Zamanaşımının Durması Defence of Extinctive Prescription Defence Objection Means of Defence in the Field of Substantive Law Means of Defence in the Field of Civil Procedure Interruption of Extinctive Prescription Suspension of Extinctive Prescription